Археозоологічний комплекс з поселення Уч-Баш - Кройтор, Р.В. (Археологія, 2012)
Вперше подано палеозоологічний матеріал кизил-кобинської культури — з поселення Уч-Баш (розкоп 1). Даны описание и анализ остеологического материала с поселения кизил-кобинской культуры Уч-Баш (середина IX — начало VII вв. до н. э.) из юго-западного Крыма. Наиболее богатым по количеству материала и видовому составу является самый поздний археозоологический комплекс — из зольника. Материал из супесчаного слоя, соответствующего периоду запустения на городище, малочисленен и беден в видовом отношении, а из наиболее древнего суглинистого слоя по своей структуре сходен с комплексом из зольника. The description and analysis of osteological material from Uch-Bash, a Kyzyl-Koba culture settlement in the South-Western Crimea, dated from the middle 9th c. to the 7th c. BC, is presented. The largest by numbers and by species composition is the latest archaeozoological assemblage from the burnt mount. The material from the sandy loam layer corresponding to the period of desolation at the settlement is scarce and barren regarding species. Archaeozoological material from the most ancient loam layer is similar in its structure with the burnt mount assemblage.